2018
DOI: 10.1088/1361-665x/aae59f
|View full text |Cite
|
Sign up to set email alerts
|

Self-healing properties of reactive powder concrete with nanofillers

Abstract: The study presented in this paper aims to investigate the self-healing properties of reactive powder concrete (RPC) modified with nanofillers, which has the self-healing ability of compressive and flexural strength. The inner damage of RPC with nanofillers during loading is analyzed by using an acoustic emission system. Three types of nanofillers (nano-SiO2, nano-TiO2 and nano-ZrO2) and two curing methods (water curing and air curing) are selected for identifying the influencing factors. Experimental results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Second, the nanofillers can help form a dense cement matrix. Third, some nanofillers, such as nano-SiO 2 , have pozzolanic reactivity, 147 which promotes the formation of dense calcium− silicate−hydrates. Siad et al 142 reported that adding 0.25−0.5% carbon nanotubes can lead to accelerated recovery of flexural strength.…”
Section: Autogenous Healing From Fibers Nanofibers and Internal Curin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the nanofillers can help form a dense cement matrix. Third, some nanofillers, such as nano-SiO 2 , have pozzolanic reactivity, 147 which promotes the formation of dense calcium− silicate−hydrates. Siad et al 142 reported that adding 0.25−0.5% carbon nanotubes can lead to accelerated recovery of flexural strength.…”
Section: Autogenous Healing From Fibers Nanofibers and Internal Curin...mentioning
confidence: 99%
“…In the meantime, more fractures were generated but with smaller crack widths. Wang et al 147 reported that the addition of inorganic nanomaterials (e.g., SiO 2 , TiO 2 , or ZrO 2 ) could enhance the cement's self-healing properties. Among those materials, nano-SiO 2 works best for the healing process.…”
Section: Autogenous Healing From Fibers Nanofibers and Internal Curin...mentioning
confidence: 99%
“…Such propagation can be inhibited by self-healing processes of cementitious materials, specifically the autogenous healing mechanism [2], which is an intrinsic repair property of cementitious material. Autogenous healing can be accelerated by applying mineral admixture [3], fiber [4,5], nanofiller [6], and curing agent [7,8]. Another self-healing concrete process is the autonomous healing, which involves the incorporation of capsules containing healing agents or bacteria spores to the composites including electrodeposition [9,10], epoxy injection [11][12][13], polymers [13][14][15], and shape-memory alloys [16].…”
Section: Introductionmentioning
confidence: 99%
“…The restless search for durability and resilience of concrete structures has led some researchers to focus on self-healing concrete composites with the built-in ability of repairing narrow cracks without human or external intervention [ 2 , 3 , 4 , 5 ]. Two major types of self-healing concretes have emerged: the autogenous type [ 4 ], which is achieved by autogenous healing materials such as mineral admixtures like ground-granulated blast-furnace slag (GGBFS), silica fume or fly ash, fibers and nanofillers [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]; and, the autonomous type [ 3 ], which is realized by unconventional engineered additions such as shape memory alloys, capsules, polymers or bacteria to seal the cracks [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Autogenous healing is an old and well-known phenomenon that originates naturally from the cementitious material like the hydration of clinker minerals or the carbonation of calcium hydroxide while autonomous healing requires a trigger to activate the process.…”
Section: Introductionmentioning
confidence: 99%